Ion exchange membrane with gradually changed thickness and application of ion exchange membrane in flow battery
By designing an ion exchange membrane with gradient thickness along the electrolyte flow direction in the liquid flow battery, the problem of low energy efficiency caused by uniform film thickness is solved, and a higher overall battery energy efficiency and battery performance improvement is achieved.
Patent Information
- Application Number
- CN202411582297.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
AI Technical Summary
The ion exchange film used in traditional flow batteries has uniform thickness, and it is impossible to fully utilize the law that the electrolyte reaction speed gradually decreases along the electrode direction, resulting in the failure to fully utilize the film performance, limiting the energy efficiency of the flow batteries.
An ion exchange membrane for flow batteries is designed, with the thickness gradually increasing along the direction of the electrolyte flow, from the thinnest at the inlet of the electrolyte to the thickest at the outlet. The specific thickness range is determined based on the type of flow battery and the type of electrolyte.
Through the gradient-thick ion exchange membrane, the comprehensive energy efficiency can be improved in the flow battery, the voltage and coulomb efficiency of the film can be improved, and the traditional uniform thickness film can be replaced, and the film production cost can be reduced.
Smart Images

Figure CN119419325A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of ion exchange membranes, in particular to an ion exchange membrane with a gradient thickness and application thereof in a liquid flow battery. Background Art
[0002] In liquid flow batteries, ion exchange membranes play the role of blocking the active materials of the positive and negative electrodes to prevent cross-mixing, while conducting ions to form a conductive circuit inside the battery. At present, there are two main types of ion exchange membranes for liquid flow batteries: homogeneous membranes and composite membranes. Homogeneous membranes refer to membrane materials whose components are uniform in the membrane surface direction and thickness direction, such as Nafion membranes; composite membranes refer to membrane materials with a certain variation in components in the thickness direction and a multilayer structure, such as Gore's ePTFE reinforced membrane. However, the components of these two membranes are consistent in the membrane surface direction. Therefore, the performance of membrane surface resistance / proton conductivity and ion selectivity at any point on the membrane surface is consistent. But the actual situation is that in the flow battery stack, the speed of the redox reaction of the electrolyte on the electrode gradually decreases along the flow direction of the electrolyte. This is because at the inlet of the electrolyte, the electrolyte reaction active substances have sufficient concentration. As the active substances in the electrolyte react and flow along the electrode, the concentration of the active substances gradually decreases, and its reaction rate will decrease, and the demand for proton exchange decreases. This also makes the reaction rate on the membrane surface positively correlated with the reaction rate of the active substances on the electrode surface, that is, it shows a certain regularity along the flow direction of the electrolyte. Therefore, we can make full use of this principle to design and develop ion exchange membranes for flow batteries in a targeted manner, which can improve the comprehensive energy efficiency of ion exchange membranes in flow battery stacks to a certain extent.
[0003] In liquid flow batteries, the ion selectivity and membrane surface resistance of the ion membrane are the two most core parameters. Under the same membrane components, the thicker the membrane thickness, the better the ion selectivity, but the larger the membrane surface resistance; the thinner the membrane thickness, the worse the ion selectivity, but the lower the membrane surface resistance. Therefore, the choice of membrane thickness is a very important factor to be considered in the selection of liquid flow battery membrane materials. Traditional liquid flow battery ion exchange membranes use ion exchange membranes with uniform thickness (generally requiring a thickness tolerance of no more than ±5%), that is, in the membrane reaction zone, the thickness of the membrane near the battery inlet and outlet is the same, which will limit the full performance of the membrane to a certain extent. Therefore, combined with the reaction rate law of liquid flow battery electrolyte on the electrode and membrane, the thickness of the ion exchange membrane can be specifically designed to meet the actual needs of liquid flow batteries and improve the energy efficiency of liquid flow batteries. Summary of the invention
[0004] In order to make up for the deficiencies of the prior art, the technical solution of the present invention is as follows:
[0005] An ion exchange membrane for a liquid flow battery. In a reaction zone of the liquid flow battery, the thickness of the ion exchange membrane gradually increases along the flow direction of the electrolyte.
[0006] like Figure 1 As shown, in liquid flow batteries / stacks, in order to ensure full utilization of the electrolyte and reduce the occurrence of dead zones, the electrolyte is usually introduced from the bottom to the top, that is, the electrolyte enters the stack from the bottom and flows out of the stack at the top, or in the reaction zone of the membrane flow battery, the electrolyte enters from the bottom inlet and is evenly distributed, flowing upward in parallel until the electrolyte outlet at the top. As described in the background introduction, the electrolyte reaction rate decreases from bottom to top. In areas where the electrolyte reaction rate is faster, the proton transmembrane exchange rate is faster, and a relatively thin membrane is required to support it in order to reduce the membrane surface resistance and improve the overall membrane voltage efficiency; in areas where the electrolyte reaction rate is slower, the proton transmembrane demand is relatively small, and a thicker ion exchange membrane can be selected, and the ion selectivity of the slower reaction rate area can be improved, thereby improving the overall membrane Coulomb efficiency.
[0007] Furthermore, the resin type constituting the ion exchange membrane is the ion exchange resin widely used in the field of liquid flow batteries, including cation exchange resin and anion exchange resin, specifically including but not limited to perfluorosulfonic acid resin, sulfonated polyetheretherketone resin, sulfonated polyethersulfone resin, polybenzimidazole ion exchange resin, etc.
[0008] Theoretically, there should be no specific restrictions on the thickness of the thinnest and thickest parts of the membrane, and the thickness range should be determined comprehensively based on the type of flow battery or electrolyte and battery operating conditions.
[0009] In a preferred embodiment, if it is a perfluorosulfonic acid ion exchange membrane, when it is used in an all-vanadium redox flow battery, in order to achieve better battery performance, the thickness of the perfluorosulfonic acid ion exchange membrane is preferably in the range of 25-80 μm, that is, the thinnest part of the membrane is preferably 25 μm, and the thickest part of the membrane is preferably 80 μm;
[0010] In a preferred embodiment, if it is a sulfonated polyetheretherketone ion exchange membrane, when it is used in an all-vanadium liquid flow battery, in order to achieve better battery performance, the thickness of the sulfonated polyetheretherketone ion exchange membrane is preferably in the range of 30-100 μm, that is, the thinnest part of the membrane reaction zone is preferably 30 μm, and the thickest part of the membrane is preferably 100 μm;
[0011] In some embodiments of the present invention, in the same membrane reaction zone, the thickness of the thickest part is preferably no more than 3 times the thickness of the thinnest part. It is worth noting here that, in theory, the gradual increase range of the membrane thickness should be determined according to the battery performance, but because the membrane edge may involve problems with battery assembly and sealing, excessive thickness variation may cause the battery assembly and sealing process to be more complicated, so the thickness of the thickest part is set to no more than 3 times the thickness of the thinnest part. However, if there are more advanced battery stack assembly and sealing technologies, the thickness of the thickest and thinnest parts of the membrane reaction should not be subject to this restriction, because the battery stack assembly and sealing technology does not involve or affect the technical creation and ideas of the ion exchange membrane body in the present invention, and does not violate the core spirit of the present invention;
[0012] Regarding the preparation method of ion exchange membranes, conventional ion exchange membranes are usually prepared using an extrusion molding method, a steel strip casting method, and a solution casting method.
[0013] For the extrusion molding method, it means heating the resin to a temperature above the melting temperature (generally lower than the thermal decomposition temperature, and inert gas protection can be used if necessary), and adjusting and ensuring the final film thickness and uniformity by regulating the extrusion temperature of each part of the extruder head outlet and the width of the extruder head gap. The present invention can utilize extrusion molding equipment to specifically adjust the temperature of each area of the extruder head (i.e., temperature gradient changes) and the width of the head gap (i.e., head gap width gradient changes) to prepare an ion exchange membrane with varying thickness. Moreover, adjusting the temperature of each area of the head and the width of the head gap are common means and methods in the field of film making, so there is no need to elaborate;
[0014] For the steel strip casting method, a uniform thickness ion exchange membrane is generally prepared by setting a fixed knife-band gap between a horizontally placed steel strip and a scraper in the membrane width direction (or in the electrolyte flow direction in a flow battery). For the present invention, the knife-band gap can be gradually increased / decreased along the membrane width direction, and then quickly transferred to a film drying device to prepare the ion exchange membrane of the present invention. Adjusting the thickness of the membrane by the knife-band gap is a common means and method in the field of membrane making, so there is no need to elaborate.
[0015] For the solution casting method, generally, a dilute resin solution is poured into a horizontal casting plate of a certain size, and the "self-leveling" of the dilute solution is used to control the uniformity of the film thickness. For the present invention, the casting plate can be set to tilt at a certain angle to make the thickness of the final film change along one direction. Therefore, the thickness adjustment method is a common means and method in the field of film making, so there is no need to elaborate.
[0016] It can be known from the above description that the preparation method can be a derivative method based on the actual film making situation, and its thickness control means are common means and methods in the film making field. Therefore, the present invention is only introduced here without any method limitation.
[0017] Another object of the present invention is to claim the application of the ion exchange membrane in a liquid flow battery, that is, when the ion exchange membrane is applied in a liquid flow battery, in the reaction zone of the liquid flow battery, the thickness of the ion exchange membrane gradually increases along the flow direction of the electrolyte. Theoretically, it can be applied to all liquid flow battery systems, especially in all-vanadium liquid flow batteries to improve the efficiency of liquid flow batteries.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention provides an ion exchange membrane with a gradient thickness, the thickness of which gradually increases along the electrolyte direction in the reaction area of the flow battery membrane. The membrane can be designed specifically according to the reaction characteristics of the flow battery, which helps to improve the overall energy efficiency of the flow battery.
[0020] (2) Compared with the existing method for preparing a membrane with uniform thickness for a liquid flow battery, the preparation method of the ion exchange membrane for the liquid flow battery of the present invention does not increase the membrane preparation cost, and only requires corresponding fine-tuning and modification of the existing equipment. The prepared membrane has more excellent battery performance and can replace the existing ion exchange membrane in the field of liquid flow battery energy storage.
[0021] Instruction Manual
[0022] Figure 1 It is a schematic diagram of the reaction zone, electrolyte flow direction and membrane thickness gradual increase direction of the membrane flow battery. DETAILED DESCRIPTION
[0023] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the examples, but the content of the present invention is not limited to the following examples. The following examples describe in more detail a gradient thickness ion exchange membrane and its application in a flow battery in the present invention, and these examples are given in an illustrative manner, but these examples do not limit the scope of the present invention. Unless otherwise specified, the experimental method used in the present invention is a conventional method, and the experimental equipment, materials, reagents, etc. used can be purchased from a chemical company.
[0024] Perfluorosulfonic acid resin (H + Sulfonated polyetheretherketone (SPEEK) resin is prepared by sulfonation reaction of polyetheretherketone powder and concentrated sulfuric acid. For details, please refer to the literature: Zhang Qingting et al., Preparation and modification of sulfonated polyetheretherketone membrane for DMFC, New Chemical Materials, 2012, 40(3), 121 or other literature. The ion exchange capacity of the sulfonated polyetheretherketone resin prepared in the present invention is 1.84mmol / g.
[0025] In the embodiments and comparative examples described in the present invention, the most mature and reliable steel strip casting process is used for the film-making process, and DMF is used as the solvent / dispersant for dissolving the resin slurry. The film-making process and parameters for preparing ion exchange membranes of the same resin type are basically the same, and only the parameters involving the thickness gradient control are slightly different, which will not have a significant impact on other process steps, so it will not be described in detail.
[0026] The thickness of the ion exchange membrane is tested by a digital micrometer;
[0027] The present invention and comparative examples use a typical liquid flow battery, the all-vanadium liquid flow battery, as an example to evaluate the performance of the ion exchange membrane liquid flow battery. The performance test conditions of the all-vanadium liquid flow energy storage battery with an ion exchange membrane are: at a current density of 160 mA / cm 2 The charge and discharge experiments were carried out under the conditions of single cycle charging to 1.55V and discharging to 1.00V. The graphite carbon felt produced by Liaoyang Jingu Carbon Materials Co., Ltd. was used as the reaction electrode. The effective working size of the electrode was 60cm×80cm. The positive and negative electrolytes were VO 2+ / VO2 + and V 2+ / V 3+ of sulfuric acid solution, the battery operating temperature is 37°C.
[0028] In the all-vanadium liquid flow battery of the following embodiments, the electrolyte flows from bottom to top along the width direction of the ion exchange membrane, that is, the thickness of the ion exchange membrane in the membrane reaction zone increases from bottom to top.
[0029] Example 1
[0030] The perfluorosulfonic acid resin ion exchange membrane described in the present invention is prepared, and the thickness of the membrane reaction zone increases in the range of 25 μm-50 μm;
[0031] Example 2
[0032] The perfluorosulfonic acid resin ion exchange membrane described in the present invention is prepared, and the thickness of the membrane reaction zone increases in the range of 27 μm-75 μm;
[0033] Example 3
[0034] The perfluorosulfonic acid resin ion exchange membrane described in the present invention is prepared, and the thickness of the membrane reaction zone increases in the range of 44 μm-80 μm;
[0035] Example 4
[0036] The perfluorosulfonic acid ion exchange membrane of the present invention is prepared, and the thickness of the membrane reaction zone increases in the range of 43 μm-62 μm;
[0037] Example 5
[0038] The sulfonated polyetheretherketone ion exchange membrane of the present invention is prepared, and the thickness of the membrane reaction zone increases in the range of 30 μm-61 μm;
[0039] Example 6
[0040] The sulfonated polyetheretherketone ion exchange membrane of the present invention is prepared, and the thickness of the membrane reaction zone increases in the range of 32 μm-78 μm;
[0041] Example 7
[0042] The sulfonated polyetheretherketone ion exchange membrane of the present invention is prepared, and its thickness increases in the range of 51 μm-100 μm;
[0043] Comparative Example 1
[0044] Preparation of a uniform thickness perfluorosulfonic acid ion exchange membrane with a thickness of 26±0.6μm
[0045] Comparative Example 2
[0046] Preparation of a uniform thickness perfluorosulfonic acid ion exchange membrane with a thickness of 52±1.4μm
[0047] Comparative Example 3
[0048] Preparation of sulfonated polyetheretherketone ion exchange membrane with uniform thickness of 74±1.2μm
[0049] Table 1 Test results of ion exchange membrane batteries prepared in various embodiments
[0050]
[0051] From the comparison between Examples 1 and 2 and Examples 5 and 6, it can be seen that within a certain range, under the condition that the minimum thickness remains basically the same, the maximum thickness is appropriately increased, that is, the thickness gradient range is expanded, the Coulomb efficiency and energy efficiency of the flow battery can be improved; but from the comparison between Examples 3 and 4, it can also be seen that although the increase in thickness improves the Coulomb efficiency, the corresponding voltage efficiency decreases more, resulting in a decrease in the final energy efficiency, which also means that the increase in the maximum thickness alone is not completely conducive to improving the energy efficiency of the battery, so it is necessary to select a suitable thickness and its range of variation in practical applications. It can be seen from Example 2 (average thickness of about 51 μm), Example 4 (average thickness of about 52.5 μm) and Comparative Example 2 (or from Example 7 (average thickness of about 75 μm) and Comparative Example 3) that under the condition of close average thickness, appropriately setting the thickness gradient increment range of the membrane helps to improve the energy efficiency of the battery, which fully reflects the design principle and idea of the present invention.
[0052] Due to the limitations of the battery materials, battery structure, battery reaction zone size and test conditions of the test battery used in the present invention, the membrane and battery performance prepared in the embodiments may not necessarily achieve the optimal results. In the actual production and application process, the appropriate ion exchange membrane thickness gradient increasing structure can be designed or selected based on comprehensive considerations based on the characteristics of the battery stack structure and operating test conditions.
[0053] It should be emphasized here that the protection scope of the present invention is not limited to the above embodiments. Any technician familiar with the technical field can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An ion exchange membrane for a flow battery, characterized in that: In the reaction zone of the flow battery, the thickness of the ion exchange membrane gradually increases along the flow direction of the electrolyte.
2. The ion exchange membrane for a flow battery according to claim 1, characterized in that: The resin type that constitutes the ion exchange membrane is ion exchange resin, which includes cation exchange resin and anion exchange resin.
3. The ion exchange membrane for a flow battery according to claim 2, characterized in that: The ion exchange resin includes, but is not limited to, perfluorosulfonic acid resin, sulfonated polyetheretherketone resin, sulfonated polyethersulfone resin, and polybenzimidazole ion exchange resin.
4. The ion exchange membrane for a flow battery according to claim 1, characterized in that: The ion exchange membrane is a perfluorosulfonic acid ion exchange membrane. When it is used in an all-vanadium liquid flow battery, the thickness of the perfluorosulfonic acid ion exchange membrane is in the range of 25-80 μm.
5. The ion exchange membrane for a flow battery according to claim 1, characterized in that: The ion exchange membrane is a sulfonated polyetheretherketone ion exchange membrane. When the sulfonated polyetheretherketone ion exchange membrane is used in the all-vanadium liquid flow battery, the thickness of the sulfonated polyetheretherketone ion exchange membrane is in the range of 30-100 μm.
6. The ion exchange membrane for a flow battery according to claim 1, characterized in that: In the same membrane reaction zone, the thickness of the thickest part of the ion exchange membrane shall not exceed 3 times the thickness of the thinnest part.
7. The ion exchange membrane for a flow battery according to claim 1, characterized in that: The preparation method of the ion exchange membrane is an extrusion molding method, a steel strip casting method or a solution casting method.
8. An application of an ion exchange membrane for a flow battery, characterized in that: Used in liquid flow batteries, especially all-vanadium liquid flow batteries.